Descriptive profile of contractile and ballast tissue in body composition of cadet and junior judo athletes partialized on longitudinal basis: pilot research - Markoviv, S.; Dopsaj, M.; Jovanovic, S.; Vukovic, M. (XX Scientific Conference.FIS COMMUNICATIONS 2017" in physical education, sport and recreation (Nis, Serbia, october 19-21st, 2017), 2017)
The aim of this paper is to define a descriptive profile of contractile and ballast tissue in body composition of cadet and junior judo athletes, using partialisation on longitudinal basis. In this research the following derived indexes were used: FMI . fat mass index, PMI . protein mass index, SMMI . skeletal muscle mass index, PFI . protein fat index, PFMI . protein fat mass index. Assessment of the body composition of the subjects in this study was performed by the method of direct multisegmental multifrequency analysis of the impedance, using the InBody 720 system. The sample of respondents consisted of 20 male judo athletes, competing in different weight categories within the cadet and junior age division within the system of individual national championships for a given age category. The results have shown that the average values of the tested variables or indexes are at the following level: 1.615 +/-.365 kg.m-2 for index of fat tissue (FMI); 4.356 +/- 0.580 kg.m-2 for protein mass index (PMI); 12.521 +/- 1.788 kg.m-2 for skeletal muscle mass index (SMMI); 4.165 +/- 2.272 kg for protein fat index (PFI); and 1.336 +/- 0.781 kg.m-2 for protein fat mass index (PFMI). By determining the characteristics of the body structure in judo athletes of cadet and junior age using the modern methodology of measuring the body composition, initial information was obtained which indicates the specificity of the variables of the body composition and the specificity of the morpho-functional characteristics of young judo athletes in this developmental period.